An investigation of the integration of information technology governance in the National Department of Tourism - Mguli, Ziphozenkosi Lwando (North-West University (South Africa), 2013)
IT governance is considered a critical enabler to a transformational government and to focus on transforming IT to meet the present and future demands, goals of the business and its customers. In the public sector, reference would be made to the government at large and the general public. To this end, the government has, through the Department of Public Services and Administration (DPSA), and as part of its initiatives to invest in IT governance, released a Circular that requires all departments to adopt an ICT Governance Framework. The Circular - Corporate Governance of ICT (CGICT) Policy Framework - maps out how governance of ICT within government entities is to be applied, structured and implemented. The aim is to ensure that departments function as effectively and efficiently as possible, to achieve their desired outcomes and thereby fulfil the government's mandate of delivering public services and goods. Despite this investment, it cannot be stated with the largest degree of certainty that the government derives benefits by getting departments to incorporate IT governance in their Strategic Plans and other Plans in order to make it an integral part of their governance, as required by the Framework. In this connection, a well-meaning government approach to investment in IT governance, meant to make the work more effective, efficient and sustainable, may negatively affect the capacity and capability of such departments from taking full advantage thereof. Since government departments are necessarily distinct, a one-size-fits-all approach to integration of IT governance may not be applicable to all circumstances. The department of Tourism, with its distinct character, mandate, customers and IT infrastructure capability, warrants an investigation to assess the degree to which it has integrated IT governance in its Strategic Plan and other plans to achieve its objectives and outcomes. This research explores this dilemma by way of investigating the extent to which the National Department of Tourism has integrated the requirements of the framework in its plans, as well as its infrastructure capability adequacy. This was done through the theoretical and practical approach to the topic. Quantitative and qualitative methods were used to collect data for this study. A questionnaire consisting of three parts has been used in the survey.
MBA, North-West University, Mahikeng Campus
Keywords: IT governance; Strategic Plan; National Department of Tourism; Policy Framework; Desired outcomes